Accepting the Judgments of the Court of Justice of the EU as Authoritative: The Supreme Court of Ireland, the European Stability Mechanism and the Importance of Legal Certainty. Issue 1 (February 2016) - Charleton, Peter; Cox, Angelina
This article discusses the contrasting constitutional models as between Ireland and Germany of accession to the European Union. Sovereign states are entitled to share a currency pursuant to treaty. Whether that potential has been lost under the European Treaties by reason of the transfer of sovereignty is the subject of decisions of the Court of justice of the European Union (Court of Justice) and the Supreme Court of Ireland. By transferring some aspect of sovereignty pursuant to international treaty, certainty of law and the principle of sovereign state equality require adherence to rulings of tribunals set up under those arrangements. In the case of the European Union, that is the Court of Justice.